An investigation of bullying of and with primary school girls: a pupil research project - Hearn, Helen (2016)
Bullying is a social phenomenon that impacts girls and boys inside and outside of school at both primary and secondary school age and is recognised as a social problem both by academic researchers and in the ‘real world’ by the media and by anti-bullying charities. Although bullying is a widely used concept there is no universal definition. Research on bullying has been conducted over the past four decades looking at various aspects from prevalence and severity to coping strategies and effectiveness of interventions. Studies have also considered specific types of bullying and sex differences but these studies do not consider the full variety of types of bullying boys and girls use or which ones are the most upsetting to experience. Most of the studies on girls’ bullying have been conducted in secondary schools; less attention has been given to tweenage girls. This research redressed this imbalance. It began from the position that it is important for adults to listen to tweenage girls’ views as they may have different understandings of bullying compared to adults and this may have policy implications. It assumed that girls were experts on bullying that happened to girls their age in their school. Weekly research lunch club sessions were used with 32 tweenage girl research advisers/assistants from three primary schools. Together we listened to tweenage girls’ views of bullying broadly through developing and administering questionnaires, conducting group interviews and designing anti-bullying resources to be used in their schools. In addition, I conducted one-off focus groups with 11 teenage girls as a comparison to consider age differences in girls’ views. I argue that this research revealed that both girls’ bullying and using pupil research to engage with tweenage girls’ views on this topic was messy and complex. While relational aggression between girls was reported to be most prevalent and severe, focusing on this alone does not reflect the full extent of the behaviours used in girls’ bullying. Both the tweenage and teenage girls’ views on bullying, coping strategies and anti-bullying interventions were similar and were only subtly different in the detail. The research decisions were influenced in an ongoing process by the wants and expectations of the girls, the schools and the researcher and changed through the prolonged interactions during the research. I also argue that ethical practice was an ongoing process and using pupil research created further ethical dilemmas. Although pupil research with tweenage girls on girls’ bullying was challenging and messy, this research gives an example of how it is a viable, successful way to engage with pupils on this sensitive topic. The use of girls’ free time at lunchtimes showed how pupil research positioned as an extra-curricular activity enabled marginalised voices to be heard and was beneficial for the girls, the schools and the researcher involved. This research suggests ways in which school based anti-bullying policies and practices might be more nuanced to take account of the variety of experiences, understandings and preferences for intervention that exist if they engaged in pupil research. There has been little discussion of the issues of the messiness of research and the ongoing nature of ethical practice in either the pupil research literature or methods texts generally for researchers to refer to. I suggest that it would be useful for others to share their messy experiences of pupil research and the ongoing ethical issues they encounter to enable future researchers to be somewhat prepared and confident in responding to the challenges they may face in their own research.